2012
DOI: 10.1017/jfm.2012.399
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of a double-diffusive interface in the diffusive convection regime

Abstract: Three-dimensional direct numerical simulations are performed that give us an in-depth account of the evolution and structure of the double-diffusive interface. We examine the diffusive convection regime, which, in the oceanographically relevant case, consists of relatively cold fresh water above warm salty water. A 'double-boundary-layer' structure is found in all of the simulations, in which the temperature (T) interface has a greater thickness than the salinity (S) interface. Therefore, thin gravitationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 41 publications
(95 reference statements)
8
68
1
Order By: Relevance
“…Hilgersom et al: An axisymmetric non-hydrostatic model for double diffusion Yoshida and Nagashima (2003) have shown that 2-D numerical models are already well able to simulate small-scale processes in laboratory set-ups. On a larger scale, Sommer et al (2014) confirm the findings of Carpenter et al (2012) with 2-D DNS and high-resolution measurements of a double-diffusive staircase in Lake Kivu for density ratios larger than 3, noting that in these systems external turbulence by shear or internal waves should be absent to maintain diffusion as the main driver for salt and heat transport. Noguchi and Niino (2010a, b) used 2-D DNS to study the spontaneous layer formation in the double-diffusive convection regime and explore the layer formation from the nonlinear evolution of disturbances.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Hilgersom et al: An axisymmetric non-hydrostatic model for double diffusion Yoshida and Nagashima (2003) have shown that 2-D numerical models are already well able to simulate small-scale processes in laboratory set-ups. On a larger scale, Sommer et al (2014) confirm the findings of Carpenter et al (2012) with 2-D DNS and high-resolution measurements of a double-diffusive staircase in Lake Kivu for density ratios larger than 3, noting that in these systems external turbulence by shear or internal waves should be absent to maintain diffusion as the main driver for salt and heat transport. Noguchi and Niino (2010a, b) used 2-D DNS to study the spontaneous layer formation in the double-diffusive convection regime and explore the layer formation from the nonlinear evolution of disturbances.…”
Section: Introductionsupporting
confidence: 75%
“…The vertical saline and thermal density fluxes across the interface, F c , are calculated on each grid location by time differentiating the salt and heat volumes above the interface according to Carpenter et al (2012):…”
Section: Validation For Double-diffusive Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations